Examining and Assessing the Students' Academic writing: an Analysis of the Students' Research papers at English Department - Faculty of Arts& Science/ Alabyar Campus. - I. G. Mohammed , Hidob (مجلة آفاق للدراسات الإنسانية والتطبيقية, 2024)
Writing in general is a complex skill, that students need to go successfully through college or university. Students whose major subject is English and who study in the final semester are believed to have challenges in producing an academic research paper. This paper attempts to analyze and evaluate the students' term papers concerning academic writing skills. Considering academic writing characteristics, the researcher examined five term papers written by undergraduate students. The study used descriptive analysis as the method of the study. The analysis of the student's corpus showed that the students' writing included different types of errors. However, the lack of academic skills was the most serious and prominent one. The most obvious weakness, noticed in students' writing, was the lack of cohesion and coherence. The study also confirms that poor writing correlates with a deficiency in writing skills. Thus, it seems that the students have low proficiency when they enrolled in the English department. Therefore, it is strongly recommended that pre-sessional courses should be provided for the new students who joined their study in the English department. As well as, the study recommends adopting an admission policy for enrollment in the English department and increasing language programs in academic writing.